Block diagonal dominant remotely operated vehicle model simulation using decentralized model predictive control. (April 2017) - Lin, Weipeng; Chin, Cheng Siong
Model predictive control on a highly coupled open-frame remotely operated vehicle system subjected to uncertain disturbances has always been a challenge. A decentralized model predictive control uses a design scaling to balance the interactions between the loops to achieve a block diagonal dominant remotely operated vehicle model is used. The numerical stability of the model predictive control algorithm improves despite the sensitivity of the control parameters on the output performance. The model predictive control gives a better two-error norm performance and more tuning options to control the velocity and position output as compared to other design scaling methods and other controllers such as proportional–integral–derivative, fuzzy logic, sliding mode, and proportional–integral plus proportional cascaded control when subjected to underwater current disturbance.